Odpowiedź :
Odpowiedź:
Ćwiczenie 2
I sposób
7 - (6 + x)/3 = 2(x - 1) + 7
7 - 2 + 1/3x = 2x - 2 + 7
5 + 1/3x = 2x + 5
1/3x - 2x = 5 - 5
(- 1 2/3)x = 0
x = 0
II sposób
7 - (6 + x)/3 = 2(x - 1) + 7 | * 3
7 * 3 - 6 - x = 3 * 2(x - 1) + 7 * 3
21 - 6 -x = 6(x - 1) + 21
15 - x = 6x - 6 + 21
15 - x = 6x + 15
- x - 6x = 15 - 15
- 7x = 0
x = 0
Ćwiczenie 3
P = a² + 2ah
2ah = P - a²
h = (P - a²)/2a dla a ≠ 0
[tex]zad.2\\\\7-\dfrac{6+x}{3} =2\cdot (x-1)+7~~~~\mid \cdot 3\\\\21-(6+x)=6\cdot (x-1)+21\\\\21-6-x=6x-6+21\\\\15-x=6x+15\\\\-x-6x=15-15\\\\-7x=0~~\mid\div(-7)\\\\x=0\\Jedynym~~rozwiazaniem~~tego~~rownania~~jest~~liczba~~0.\\\\Sprawdzanie:\\\\L=7-\dfrac{6+0}{3}=7-\dfrac{6}{3}=7-2=5\\\\P=2\cdot (0-1)+7=2\cdot (-1)+7=-2+7=5\\\\L=P ~~cbdu.[/tex]
[tex]zad.3\\\\P=a^{2} +2\cdot a\cdot h~~\land ~~a\neq 0\\\\a^{2} +2\cdot a\cdot h=P\\\\2\cdot a\cdot h=P-a^{2} ~~\mid \div ~~(2\cdot a)\\\\h=\dfrac{P-a^{2} }{2\cdot a} \\\\h=\dfrac{1}{2} \cdot \dfrac{P}{a} -\dfrac{1}{2}\cdot a~~~~zal.~~a\neq 0[/tex]